(untitled) (The Mega Journal, 2024)
A key element in maintaining human health is the quality of drinking water which is a vital component of natural resources. This study was conducted to assess the ground water quality in the Kathmandu Valley and Siraha district from October 2022 to March 2023 in the Water Engineering and Training Centre, Ratopul, Kathmandu. A total of 123 water samples were collected from various wells and borings around the Kathmandu Valley and Siraha district and were subjected to physicochemical investigation following the standard techniques for water sample collection and analyzed by methods as described in the American Public Health Association (1998). The pH, conductivity, turbidity, ammonia concentration, and iron content were found to exceed National Drinking Water Quality Standard guidelines value in 21.95%, 3.25 %, 53.65 %, 47.15 %, and 18.7 % of total water samples respectively. All water samples had total hardness and chloride levels within the acceptable range. The arsenic content of all samples except one well water sample from Siraha was found within a permissible level. The findings suggest that water quality is not satisfactory, which could lead to various water-borne illnesses. Therefore, proper water purification techniques should be used before consumption.